THE PLASTIC WASTE CRISIS IN INDONESIA AND THAILAND: CHALLENGES, ENVIRONMENTAL IMPACTS, AND SUSTAINABLE SOLUTIONS - Nurhanifah, Aulia; Hotimah, Oot; Agustine, Elma Amalia; Febianto, Bunga (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The plastic waste crisis in Indonesia and Thailand is one of the biggest environmental challenges in Southeast Asia, triggered by increased plastic consumption due to urbanization, economic growth and modern lifestyles. This study aims to analyze the challenges, environmental impacts, and sustainable solutions related to plastic waste management in both countries. The method used is qualitative analysis based on secondary data from scientific literature, reports of international institutions. The results show that Indonesia faces serious problems in plastic waste management that cause marine pollution to other countries, while Thailand struggles with the high volume of domestic and imported plastic waste. The resulting environmental impacts include damage to marine ecosystems, threats to biodiversity, and human health risks from microplastics. Recommended solutions include the implementation of national regulations that support sustainability principles, 3R (Reduce, Reuse, Recycle) strategies, promotion of eco-friendly packaging, and public education to reduce the use of single-use plastics. The study concludes that regional collaboration among ASEAN countries is needed to effectively address the plastic waste crisis to protect ecosystems and human health in the long term.